Biodegradation of crude oil using self-immobilized hydrocarbonoclastic deep sea bacterial consortium. (September 2019) - Ganesh Kumar, A.; Nivedha Rajan, N.; Kirubagaran, R.; Dharani, G.
Abstract: Hydrocarbonoclastic bacterial consortium that utilizes crude oil as carbon and energy source was isolated from marine sediment collected at a depth of 2100 m. Molecular characterization by 16S rRNA gene sequences confirmed that these isolates as Oceanobacillus sp., Nesiotobacter sp., Ruegeria sp., Photobacterium sp., Enterobacter sp., Haererehalobacter sp., Exiguobacterium sp., Acinetobacter sp. and Pseudoalteromonas sp. Self-immobilized consortium degraded more than 85% of total hydrocarbons after 10 days of incubation with 1% (v/v) of crude oil and 0.05% (v/v) of Tween 80 (non-ionic surfactant) at 28 ± 2 °C. The addition of nitrogen and phosphorus sources separately i.e. 0.1% (v/v) of CO (NH2 )2 or K2 HPO4 enhanced the hydrocarbon utilization percentage. The pathways of microbial degradation of hydrocarbons were confirmed by FTIR, GC–MS, 1 H and 13 C NMR spectroscopy analyses. These results demonstrated a novel approach using hydrocarbonoclastic self-immobilized deep sea bacterial consortium for eco-friendly bioremediation. Graphical abstract: Unlabelled Image Highlights: Self-Immobilized hydrocarbonoclastic deep sea bacterial consortium effectively degraded crude oil. Immobilized cells exhibited enhanced crude oil degradation efficiency with supplementation of nitrogen and phosphorus sources. As a non-accumulant, the immobilized cells possess promising application in marine oil spill bioremediation.